2013
DOI: 10.2478/s11534-013-0253-x
|View full text |Cite
|
Sign up to set email alerts
|

Interacting generalized ghost dark energy in a non-flat universe

Abstract: Abstract:We investigate the generalized Quantum Chromodynamics (QCD) ghost model of dark energy in the framework of Einstein gravity. First, we study the non-interacting generalized ghost dark energy in a flat Friedmann-Robertson-Walker (FRW) background. We obtain the equation of state parameter, D = /ρ, the deceleration parameter, and the evolution equation of the generalized ghost dark energy. We find that, in this case, D cannot cross the phantom line ( D > −1) and eventually the universe approaches a deSit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 83 publications
3
12
0
Order By: Relevance
“…To address the problem of accounting for the accelerated expansion of the universe and due to an absence of knowledge in this domain, theoretical cosmologists have considered a variety of dark matter candidates to explain this phenomenon. The ghost dark matter (GDE) model which was proposed by Urban and Zhitnitsky [33][34][35][36] as well as N. Ohta [37] has been studied in several papers [44,48,49]. Without introducing further unknown degrees of freedom, this model predicts cosmic expansion based on dark energy with a correct magnitude.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…To address the problem of accounting for the accelerated expansion of the universe and due to an absence of knowledge in this domain, theoretical cosmologists have considered a variety of dark matter candidates to explain this phenomenon. The ghost dark matter (GDE) model which was proposed by Urban and Zhitnitsky [33][34][35][36] as well as N. Ohta [37] has been studied in several papers [44,48,49]. Without introducing further unknown degrees of freedom, this model predicts cosmic expansion based on dark energy with a correct magnitude.…”
Section: Summary and Discussionmentioning
confidence: 99%
“…Upto now, this model was investigated by different cosmological parameters such as EoS parameter, deceleration, ω −ω , statefinder and squared speed of sound etc. [26,[43][44][45][46]. Its generalized version in terms of PDE is defined as follows [26] …”
Section: Non-flat Frw Universe and Basic Equationsmentioning
confidence: 99%
“…Combining relations ( 7) and ( 8) with continuity equation ( 3), and solving the resulting equation for w D , we find where ξ = 8πGβ/3. When △ G = 0, we obtain the equation of state parameter of GGDE [31],…”
Section: Ggde Model With Varying Gravitational Constantmentioning
confidence: 99%
“…It was also shown that considering this term leads to a better agreement with observational data [29]. The GDE with sub-leading term H 2 is usually called generalized ghost dark energy (GGDE) and various aspects of it has been investigated in the literature [30,31].…”
Section: Introductionmentioning
confidence: 99%